Descriptive analysis of key determinants of postgraduate education quality in Cambodian universities - Wiputra Cendana; Keun Im; Joy Trison Zebua (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study presents a comprehensive descriptive analysis of the core determinants influencing postgraduate education quality in Cambodia. Drawing on empirical data from 431 postgraduate students across three leading Cambodian universities, we examine how curriculum structure, faculty competency, research environment, quality assurance, institutional resources, and student satisfaction shape educational experiences. The analysis is anchored in robust theoretical frameworks and employs validated measurement instruments. Results provide foundational insights that inform educational leadership, policymaking, and future research in developing country contexts.